Surveillance of Rubella in female students in Medical Colleges - Bahram Mazhari, Humaira Zafar, Wajiha Raza, Sumaira Zareef, Muhammed Umer Awan, Abbas Hayat (Journal of Rawalpindi Medical College, 2009)
Background: Rubella virus infection is normally not a serious infection in childhood, but if it occurs during pregnancy it can be a very serious threat to the developing fetus. It may lead to Congenital Rubella Syndrome resulting in infant mortality. Methods: This cross sectional study was conducted in Microbiology Department, Benazir Bhutto Hospital (BBH), Rawalpindi.One hundred females with their age group ranging from 17-25 years were included in the study. Twenty female medical students studying in each year of different Medical Colleges were tested. Blood samples were taken and tested for Anti Rubella Antibodies (IgG) by ELISA method. Results: Out of 100 females from Medical Colleges who were studied 54 females were found positive (54%) for IgG Anti Rubella Ab whereas 46 females (46%) were found negative. 4 students (20%) from 1st year, 7 student (35%) from 2nd year, 12 students (60%) from 3rd year, 14 students (70%) from 4th year and 18 students (90%) from final year were found Seropositive for IgG Anti Rubella Antibodies. Conclusion: Female students exposed to hospital environment develop antibodies during exposure to patients. Rubella immunization should be considered for the age group that is not exposed to the hospital environment.